PARIWISATA RELAWAN (VOLUNTEER TOURISM): PERKEMBANGAN, AKTIVITAS DAN MASYARAKAT LOKAL - I Gusti Ngurah Agung Suprastayasa (JURNAL KEPARIWISATAAN, 2011)
One of the forms of tourism that experience significant development in therecent years is volunteer tourism. The development has attracted both-theindustries as well as researchers in tourism sector. Volunteer tourism startedwhen the establishment of Volunteer Services Oversees (VSO) and US PeaceCorp which send volunteers to less developed nations for development. Thevolunteers can be involved in different areas like archeology, biology, construction, teaching, and conser vation. Compared to other forms of tourism, itis considered as an alternative, sustainable, culturally aware and environmentallyfriendly form of tourism which take into consideration and benefit the localcommunity. However researchs in different aspects of volunteer tourism needfurther be conducted.